The Malay Organization’s Strategies in Maintaining the Local Wisdom After Covid-19 in Kapuas Hulu - Suprianto, Bibi; Ibrahim, Ibrahim (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2024)
The strategy of the Malay Muslim organization in maintaining the values of local wisdom after Covid 19 has become the goal of developing the local cultural values of the Malay community. Until now, many scientists want to explore Malay community research in various scientific aspects. However, only a few researchers have investigated the mechanism of the Malay Muslim organization's strategy in maintaining the values of post-covid-19 local wisdom. The purpose of this study is to examine how Malay Muslim organizations maintain local wisdom values after COVID-19 in Kapuas Hulu. This study uses field observations, online and offline interviews, of the Malay community and members of the Malay Muslim Organization or the Malay Cultural Customary Council in Kapuas Hulu Regency. The results of this study indicate that Malay Muslim organizations in maintaining the values of post-covid-19 local wisdom in Kapuas Hulu; 1) There are restrictions on the activities of local Malay cultures; 2) Creating harmonious relations among Malay ethnic groups; 3) creating a space for re-communication of customs, ta'lim and youth meetings in the village; 4) presenting the value of art and Islamic beliefs in every tradition and culture. The findings of this study indicate that the strategy of the Malay Muslim organization in maintaining the values of local wisdom after COVID-19 has become an aspiration for local people to be enthusiastic in developing local cultures again.